2011
DOI: 10.1016/j.tube.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping did not evidence any contribution of Mycobacterium bovis to human tuberculosis in Brazil

Abstract: The contribution of Mycobacterium bovis to the global burden of tuberculosis (TB) in man is likely to be underestimated due to its dysgonic growth characteristics and because of the absence of pyruvate in most used media is disadvantageous for its primary isolation. In Brazil Mycobacterium culture, identification and susceptibility tests are performed only in TB reference centers, usually for selected cases. Moreover, solid, egg-based, glycerol-containing (without pyruvate supplementation) Löwenstein-Jensen (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…Studies in Mexico have reported a greater prevalence, with annual rates of up to 40% [4]. In Brazil, published studies on this issue are rare, and some of them did not find M. bovis strains in samples of human tuberculosis [5,6]. In contrast, a study in the state of Minas Gerais showed that M. bovis accounted for 1.6% of the mycobacterial isolates obtained from patients with tuberculosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Mexico have reported a greater prevalence, with annual rates of up to 40% [4]. In Brazil, published studies on this issue are rare, and some of them did not find M. bovis strains in samples of human tuberculosis [5,6]. In contrast, a study in the state of Minas Gerais showed that M. bovis accounted for 1.6% of the mycobacterial isolates obtained from patients with tuberculosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, infection in humans is generally not confirmed by isolation and identification of the agent, making it impossible to identify the possible source of infection. In addition, the human diseases caused by M. tuberculosis and M. bovis are indistinguishable using clinical, radiological and pathological methods (ROCHA et al, 2011). Transmission of M. bovis to humans occurs through consumption of raw milk and dairy products, or through contact with secretions from fistulated abscesses.…”
mentioning
confidence: 99%
“…36 In previous studies, we described that the clonally derived RD Rio strains of M. tuberculosis are defined by a ~26.3 kb deletion resulting in the loss or modification of 10 genes, including two preproenkephalin genes known to be recognized by host immunity. 7 In prior publications from our group, insertion sequence (IS) 6110 restriction fragment length polymorphism and MIRU-VNTR typing showed that the RD Rio sublineage likely occurred at a more distant evolutionary time, as both methods indicated considerable divergence, while it remains in the Euro-American M. tuberculosis lineage as well as belonging to the single nucleotide polymorphism Cluster VI grouping.…”
mentioning
confidence: 99%